1999
DOI: 10.1097/00000539-199904000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lidocaine for Preventing the Withdrawal Associated with the Injection of Rocuronium in Children and Adolescents

Abstract: Pain on injection of rocuronium in pediatric patients can be alleviated by pretreatment with i.v. lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 4 publications
4
91
0
4
Order By: Relevance
“…Bu amaçla lidokain, esmolol, ketamin, opioidler, deksmedotimidin, asetaminofen, nötralize edilmiş rokuronyum, dilüsyon metodu gibi tedavi modaliteleri denenmiştir. [2,[23][24][25][26] Bu çalışma bazı limitasyonlar içermektedir. Bunlar arasında uygulanan roküronyum dilüe edilmeden ve infüzyon pompası kullanılmadan IV verilmiştir.…”
Section: Tablo 2 Grupların çEkme Yanıt Skoru Dağılımıunclassified
“…Bu amaçla lidokain, esmolol, ketamin, opioidler, deksmedotimidin, asetaminofen, nötralize edilmiş rokuronyum, dilüsyon metodu gibi tedavi modaliteleri denenmiştir. [2,[23][24][25][26] Bu çalışma bazı limitasyonlar içermektedir. Bunlar arasında uygulanan roküronyum dilüe edilmeden ve infüzyon pompası kullanılmadan IV verilmiştir.…”
Section: Tablo 2 Grupların çEkme Yanıt Skoru Dağılımıunclassified
“…These include diluting rocuronium, administering it as an infusion rather than as a bolus injection and the use of other medications like lignocaine (5) antiemetics, (6) antihistaminics, (7) short acting opioids (8) sodium bicarbonate, (9) ketamine, (10) dexmedetomidine, (11) and esmolol.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is observed that the intravenous injection of rocuronium after the induction of anaesthesia is often associated with a localised withdrawal of the arm or generalised movement suggesting the presence of intense nociception, even during anaesthesia. 3,4,5,6,7 Such movements have been reported to be secondary to discomfort or pain at the site of injection in conscious patients. 8,9,10,11,12,13,14,15 Such spontaneous movements during induction can cause dislodgement of the intravenous catheter or rarely even pulmonary aspiration secondary to gastric regurgitation after generalised spontaneous movements during rocuronium injection.…”
Section: Introductionmentioning
confidence: 99%